Representasi Folklor Bali Dalam Video Game Pamali: The Hungry Witch - Thabathaba’I S, Ahmad; Putra, Ricky Widyananda (Urban: Jurnal Seni Urban, 2021)
The creative video game industry continues to grow and is in demand by the public, one of which is as an interactive entertainment medium. The following article will present an overview of the representation of Balinese folklore in the video game Pamali: The Hungry Witch which was developed by Studio Storytale. The analysis in this paper focuses on the visual aspect which is one of the main factors in a video game. The visual aspect of the corpus of data studied was reviewed with a semiotic approach initiated by Roland Bhartes. The research method used in this study is a qualitative descriptive method. The results of the study show that there are denotative, connotative, and mythical meanings of the games studied which are closely related to the traditions and culture that developed in Indonesia, especially on the island of Bali about the figure of Leak. In addition, the narrative and visual analysis of the video game Pamali: The Hungry Witch also shows the mindset, perspective, and collective memory of the Indonesian people regarding mystical things (occult).Industri kreatif video game terus berkembang dan diminati oleh masyarakat salah satunya sebagai media hiburan interaktif. Tulisan berikut ini akan menghadirkan tinjauan representasi folklor Bali dalam video game Pamali: The Hungry Witch yang digarap oleh Studio Storytale. Analisis pada tulisan ini menitikberatkan pada aspek visual yang merupakan salah satu faktor utama dalam sebuah video game. Aspek visual pada korpus data yang diteliti ditinjau dengan pendekatan semiotika yang digagas oleh Roland Bhartes. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif. Hasil penelitian memperlihatkan bahwa terdapat makna denotatif, konotatif, dan mitos dari game yang diteliti yang berkaitan erat dengan tradisi dan budaya yang berkembang di Indonesia, khususnya di Pulau Bali tentang sosok Leak. Selain itu, analisis narasi dan visual pada video game Pamali: The Hungry Witch juga memperlihatkan tentang pola pikir, cara pandang, dan memori kolektif masyarakat Indonesia mengenai hal-hal mistis (gaib).